Le discours sur le courage et sur la peur à l'époque de la renaissance - Delumeau, Jean (1974)
In readin g th e historica l literatur e o n th e Renaissanc e an d th eReformation, on e get s th e impressio n tha t Spai n an d Portuga l ha drelatively littl e t o offer , an d tha t theolog y particularl y wa s a learne denterprise tha t flourishe d onl y i n certai n soils , particularl y thos e nea rRome. America n experienc e an d American problems receive d almos tno attentio n a t th e Counci l o f Tren t (1545-1563) , tha t grea t ecume -nical gathering of bishops which was probabl y the mos t thoroughgoingreform in the history of the Roman Catholic Church. Th e Council wasprincipally concerned t o launch a theological attack on the Protestants ,and the powerfu l Jesuit s ha d no t ye t develope d muc h interes t i n Ne wWorld problems.